A scientometric analysis of entrepreneurship research in the age of COVID-19 pandemic - Francis Lwesya; Eliza Mwakasangula (Future Business Journal)
Abstract This article conducted a scientometric analysis of entrepreneurship research during the COVID-19 pandemic and its aftermath. The results show that the research focused on four thematic research clusters, namely (a) entrepreneurship and crisis management (b) social entrepreneurship and collaborative networks (c) entrepreneurship and entrepreneurial intentions, and (d) entrepreneurship and adaptation measures to the COVID-19 pandemic. Our analysis shows that while the COVID-19 pandemic has had significant negative impacts on entrepreneurship, innovation, digital transformation, resilience and adaptability, dynamic capabilities and organisational learning, collaborative networks, government support and customer-centric approaches enabled entrepreneurs to navigate the crisis. The review highlights the role of digital technologies, self-efficacy, organisational resilience, social entrepreneurship and entrepreneurship education in promoting small business development in the post-pandemic era.